Coapplication of water treatment residual and compost for increased phosphorus availability in arable sandy soils. Issue 1 (18th February 2023) - Gwandu, Tariro; Lukashe, Noxolo S.; Rurinda, Jairos; Stone, Wendy; Chivasa, Stephen; Clarke, Catherine E.; Nezomba, Hatirarami; Mtambanengwe, Florence; Mapfumo, Paul; Steytler, Jan G.; Johnson, Karen L.
Abstract: Introduction: Soil degradation coupled with poor access to organic nutrient resources remains a major constraint in increased crop productivity in sub‐Saharan Africa, thus hindering the continent's efforts in achieving the United Nations' Sustainable Development Goals, particularly goals 1 (end poverty), 2 (zero hunger) and 3 (improve human health). Water treatment residual (WTR), a by‐product of clean water treatment, has been identified as an alternative organic nutrient resource for crop production. However, there are some inconsistences in soil phosphorus (P) dynamics following aluminium WTR (Al‐WTR) application. Materials & Methods: A laboratory experiment was conducted to evaluate the P sorption of a sandy soil amended with 10% Al‐WTR, 10% compost (C) as a quasi‐control, 10% C + 10% Al‐WTR (10% coamendment) and 5% C + 5% Al‐WTR (5% coamendment) under varying levels of pH, particle size and P concentration. We calculated crop P fertilizer requirements under different amendments. Results: The results demonstrated that all amendments exceeded the minimum of 0.2 mg P L −1 needed in soil solution at equilibrium to maintain plant growth. However, the maximum P sorption capacity was higher for 10% Al‐WTR single amendment, ranging from 770 to 1000 mg P Kg −1, and from 714 to 1000 mg P Kg −1 and 555 to 909 mg P Kg −1 for 10% and 5% coamendments, respectively, across a range of pH and soil particle size fractions. The coamendments showed a reduction in crop P fertilizer requirements by ranges of 30–60% and 60–70% for the 10% and 5% coamendment levels, respectively, across different pH and particle sizes, relative to 10% Al‐WTR. Conclusion: Results show that the use of 5% coamendment in sandy soils increases P availability sufficiently to improve crop yields. The results provide scope for using Al‐WTR coamendments to rebuild soil health in sandy soils in urban agriculture and increase macronutrient provision in crops to support human health.